English as a lingua franca in china-based workplace communication - Yao Yao; Bertha Du Babcock (Ibérica, 2020)
This paper reports the findings of a multifaceted investigation into the communicative needs of using English as a business lingua franca (or BELF) in three types of companies in Mainland China: state-owned, privately-owned, and multinational companies. The findings were derived from online questionnaires and semi-structured interviews with Chinese business professionals. The findings suggest that English has played an increasingly important role in the workplace communication in Mainland China, especially in multinational companies. Using English has become a business convention in multinational companies, although the extent of its use differs depending on various contextual factors, primary among which are a professional’s duties and English proficiency. The findings also illustrate that culture plays a role as important as language in BELF communication at work. For example, social interaction, due to both cultural and linguistic reasons, has long been an issue concerning and challenging Chinese business professionals. Cultural differences may not be an insurmountable barrier, but the lack of cultural sensitivity and knowledge can cause a disruption in communication or lower the chance of promotion in a company